PENGARUH RELATED PARTY TRANSACTION DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - RICHARD RICHARD; MEINIE SUSANTY (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
The purpose of this study is to obtain empirical evidence related to the effect of company size, institutional ownership, audit committee, related party transaction, profitability, leverage, capital intensity, and inventory intensity on tax avoidance. The data used in this study are companies in the manufacturing sectors that are consistently listed in Indonesian Stock Exchange from 2021 to 2023. The research sample was selected using purposive sampling method and generates 171 years of data from 57 sample company. The data obtained from the samples were analyzed using multiple regression methods. The result of this study shows that audit committee affect on tax avoidance while company size, institutional ownership, related party transaction, profitability, leverage, capital intensity, and inventory intensity have no significant influence on tax avoidance.